2020
DOI: 10.1371/journal.pone.0234670
|View full text |Cite
|
Sign up to set email alerts
|

A novel prevascularized tissue-engineered chamber as a site for allogeneic and xenogeneic islet transplantation to establish a bioartificial pancreas

Abstract: Although sites for clinical or experimental islet transplantation are well established, pancreatic islet survival and function in these locations remain unsatisfactory. A possible factor that might account for this outcome is local hypoxia caused by the limited blood supply. Here, we modified a prevascularized tissue-engineered chamber (TEC) that facilitated the viability and function of the seeded islets in vivo by providing a microvascular network prior to transplantation. TECs were created, filled with Grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…They were positioned in a silicone cylinder tubing at the mouse groin, which was closed at the distal end with inguinal fat and completely sealed with bone wax. The study showed the ability of the chamber to obtain a microvascularized network after 28 days and to sustain the engraftment and function of syngeneic islets after 10–14 days ( 101 , 102 ). However, the use of Matrigel in clinical procedures has some shortcomings related to its poorly defined chemical composition ( 25 ).…”
Section: Tuning the Endocrine Nichementioning
confidence: 99%
“…They were positioned in a silicone cylinder tubing at the mouse groin, which was closed at the distal end with inguinal fat and completely sealed with bone wax. The study showed the ability of the chamber to obtain a microvascularized network after 28 days and to sustain the engraftment and function of syngeneic islets after 10–14 days ( 101 , 102 ). However, the use of Matrigel in clinical procedures has some shortcomings related to its poorly defined chemical composition ( 25 ).…”
Section: Tuning the Endocrine Nichementioning
confidence: 99%
“…Another approach currently undertaken is by using a preimplantation period to allow vascularization of an immunoisolated device or of a scaffold that can bear immunoisolated islets [100,101]. In the preimplantation strategy, the immunoisolating device is first implanted to allow neovascularization and afterwards immunoisolated islets are introduced [100,102]. In one of these approaches, basic fibroblast growth factor (bFGF)/sodium hyaluronateimpregnated bioabsorbable gelatin sheets were implanted subcutaneously, followed by islet transplantation 7 days after administering the bFGF mixture.…”
Section: Attraction Of Blood Vessels To Capsules and Enhancing Functi...mentioning
confidence: 99%
“…Administration of monoclonal antibody (mAbs) that specifically target molecules associated with immune reactions has been shown to prolong graft survival of various organs and tissues [133]. The mAbs include anti-CD40 mAb, anti-CD154 mAb, and anti-lymphocyte functionassociated antigen 1 (LFA-1) mAb [102,[154][155][156]. Short-term administration of anti-LFA-1 mAb combined with conformal PEG coating encapsulation synergistically elevated graft survival rates to 78% by decreasing immune cell recruitment, suppressing proinflammatory cytokines, and enhancing macrophage polarization towards an immunosuppressive M2 phenotype [155].…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%